Perencanaan Sumur Resapan Air Hujan dalam Upaya Konservasi Daerah Pesisir - Labdul, Barry Yusuf; Alitu, Aryati; Tambipi, Nur Atika (Universitas Negeri Gorontalo, 2023)
Infiltration wells are engineered construction designed for water conservation to accomodate and absorb surface water. Water conservation in necessary to reduce seawater intrusion in coastal areas. Shallow groundwater in Pohe village, located in a coastal a rea, is affected by seawater intrusion. This research aiams to converse groundwater in the coastal area and to reduce rainwater runoff that flows into drainage channels as well as to reduce seawater intrusion. The research is conducted in a coastal area in Pohe Village that is directly adjacent to Tomini Bay. The data are in the form of infiltration rate and soil permeability as the primary data and in form of rainfall in tensity betweet 2019 and 2020 as the secondary data. Infiltration rate data are obtained by useing a Double Ring Infiltrometer and are analyzed using the Horton method. Fourthermore, soil permeability data are tested using the constant head test. Analysis of rainfall intensity uses the Mononobe method, whereas discharge analysis employs th Rational method. The dimension of infiltration wells uses Sunjoto 1988 method.Findings reveal that the infiltration rate (ft) at the research site is 3.89 cm/hour or 38,90 mm/hour which is classified as moderate criteria. The coefficient of soil permeability (k) is 0.07 cm/second. Rain intensity (I) obtains 38.94 mm/hour. According to the data, the area of Pohe Village (A) is 4.83 km2 and the flow coefficient (C) is 0.21. The discharge analysis (Q) is 10.86 m3/second. The dimension of the infiltration wells is planned to use a cylindrical shape with a diameter of (D) 1 m and a depth of (H) 58.90 m. The are 31 wells with a depth of 1.90 m.